Technical-economic evaluation of the use of biopolymers for the treatment of wastewater from tanneries - Basurto-Flores, Nickole (2023)
[Introduction]: For years, wastewater from tanneries has been discharged into various water sources without any control or with inefficient technologies, generating an impact on water quality. [Objective]: To evaluate the technical-economic feasibility of the use of the biopolymer pectin and chitosan for the treatment of tannery wastewater. [Methods]: Extraction of pectin from cocona and chitosan from shrimp was performed. A jar test was performed where the wastewater and biopolymers were combined, the agitation speed was 120 rpm and the contact time was 1, 2 and 3 h. Analyses of pH, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS) and Cr+6 were performed on the samples obtained. For comparison with Maximum Allowable Values (MAV), the samples that showed the highest TSS and Cr+6 removal were used. For the statistical analysis of the different times and concentrations an ANOVA and multiple comparison test was performed, for the comparison of efficiencies between pectin and chitosan a Student's t-test was performed.[Results]: In the amount of 1 g of both chitosan and pectin there was a removal of Cr+6 of 98.33 % and 98.30 % respectively, both with a time of 1 h, in total suspended solids there was a reduction of 98 % with 1 h of mixing for pectin and 96 % with 3 h of mixing using chitosan. The removal efficiency between chitosan and pectin did not show a significant difference. In the economic part there is a saving of 846.85 USD while for chitosan there would be a saving of 807.61 USD. The concentration of settleable solids and oils and fats parameters were found to be within the VMA. However, for sulfides, BOD and COD were not met. [Conclusions]: With the use of biopolymers, a considerable decrease in Cr+6 and TSS was achieved, in addition to the fact that both proved to be very efficient. It is also a more economically profitable technology compared to the technology used by the tannery studied; however, in order to meet the requirements of the VMA, some additional technologies must be used.